OWNERSHIP STRUCTURE, FIRM VALUE AND THE MODERATING EFFECTS OF FIRM SIZE: EMPIRICAL EVIDENCE FROM INDONESIAN CONSUMER GOODS INDUSTRY - Iman Sofian Suriawinata; Denty Melatijati Nurmalita (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2022)
Employing a panel data from a sample of Indonesia listed consumer goods companies covering the period of 2015-2019, the present study examines the effect of share ownership structure on firm value with firm size acting as a moderating variable. The estimation results show that while the control hypothesis of institutional ownership is supported, the alignment hypothesis of managerial ownership does not hold. However, the present study finds that firm size moderates the effect of share ownership structure on firm value. As firm size increases, managerial conducts are more inclined to conform with shareholders’ interest. But on the other hand, as firm size increases, institutional investors tend to side with managers in extracting more value at the expense of other shareholders. These findings corroborate anecdotal evidence in empirical corporate finance that size does matter, and provides insights for policy makers relating to corporate governance implications of institutional ownership in large firms.